Processing rice bran to yield added-value oil based extracts - Nantiyakul, Nantaprapa (2012)
Rice bran, a by-product from rice milling, is an excellent source of natural antioxidants. Lipids in rice bran appear as small spherical droplets called oil bodies. This work attempted to recover the oil bodies from rice bran (fresh, stored and heat-treated) and to determine their chemical, biochemical and physical properties ex vivo. As revealed by transmission electron microscopy, oil bodies were observed mainly in the sub-aleurone and aleurone layer of brown rice. Oil bodies were successfully recovered from rice bran and were enriched in tocochromanols and oryzanol (656 - 1,006 mg/kg lipid and 8,880 - 9,692 mg/kg lipid respectively). Further washing to remove extraneous protein and non-associated compounds, effective lipid concentration increased while protein concentration decreased. The washed oil body preparation contained approximately 35 - 68 % tocochromanols and 60 - 62 % oryzanol of the parent rice bran oil. Therefore, the majority of tocochromanols and oryzanol molecules appeared to be intrinsically associated with rice bran oil bodies ex vivo. Fatty acid composition of rice bran oil bodies was similar to that of parent rice bran. SDS-PAGE of proteins present in differentially washed oil body preparations revealed similar protein profiles; however, there was a relative enrichment of the bands at 16 - 18 kDa (typical molecular weight of oleosins). Rice bran oil bodies possessed negatively charged surface (-30 mV) at neutral pH. As the pH of the oil body suspension was lowered to the pH near pI (about pH 4 - 5), zeta potential of the oil bodies approached zero and the suspension had the least physical stability; aggregation and the least relative turbidity. The biochemical instability of rice occurs immediately after milling, which leads to the limited use of rice bran for human consumption. Free fatty acids and lipid hydroperoxides in rice bran and corresponding oil bodies increased significantly (P<0.05) during storage. Oil bodies recovered from stored rice bran aggregated and coalesced. 41% of tocochromanols in the oil bodies had decomposed while the concentration of oryzanol was relatively stable during the storage. Rice bran heat treatments (pan roasting and extrusion) caused the coalescence of oil bodies in vivo and the instability of an oil body suspension ex vivo. The main findings of this study were that rice bran oil bodies were enriched in phytochemicals including tocochromanols and oryzanol and were resistant to oxidation providing that the oil bodies were still intact. The oil bodies could delay the onset of lipid oxidation of stored lipids inside the oil bodies. This may be explained by the physical barrier of surface membrane protein (oleosin) against pro-oxidants and the intrinsic association between the oil bodies and phytochemicals in rice bran.